ANALYSIS COMMUNITY ENERGY BEHAVIOR ENVIRONMENTALLY (International Conference on Social and Islamic Studies, 2021)
The increasing consumption of electrical energy coupled with the dwindling availability of fossil energy sources has resulted in a world energy crisis, especially in Indonesia. The government has begun to take solution steps to save the world's energy, such as policies to use renewable energy as alternative energy and energy conservation. The purpose of this study is to identify the energy-saving behaviour of the community as a step to follow government regulations regarding the implementation of energy conservation. By using a quantitative approach, this study also aims to determine what factors encourage a person to consume electrical energy that is environmentally sound. Environmentally sound energy behaviour is expected to be one of the solutions in solving the problem of the world energy crisis in addition to the use of renewable energy as alternative energy and a benchmark for public awareness of energy problems.